2009
DOI: 10.1007/s00330-009-1552-x
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric quantification of myocardial perfusion using analysis of multi-detector computed tomography 3D datasets: comparison with nuclear perfusion imaging

Abstract: Our new technique for volumetric analysis of 3D MDCT images allows accurate objective detection of perfusion defects. This perfusion information can be obtained without additional radiation or contrast load, and may aid in elucidating the significance of coronary lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 30 publications
2
18
0
Order By: Relevance
“…Figure 7 shows the mean attenuations obtained for all segments. Notice the wave-like variation among segments, consistent with analogous results obtained by Kachenoura et al [2]. Considering the small number of patients involved, these are preliminary results and we aim to extend this study to a larger population.…”
Section: Segmental Attenuation Histogramsupporting
confidence: 91%
See 3 more Smart Citations
“…Figure 7 shows the mean attenuations obtained for all segments. Notice the wave-like variation among segments, consistent with analogous results obtained by Kachenoura et al [2]. Considering the small number of patients involved, these are preliminary results and we aim to extend this study to a larger population.…”
Section: Segmental Attenuation Histogramsupporting
confidence: 91%
“…As proposed by Kachenoura et al [2] using a mixed index accounting for severity (how low the attenuation goes) and volume (how much voxels are below the reference) of the lesions leads to a good distinction between healthy and hypoperfused segments. Furthermore, this method also allows proper adjustments considering the naturally occurring mean attenuation differences among myocardial segments.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Beginning in 2005, different authors [1,[7][8][9] attempted perfusion imaging with CT under resting conditions to evaluate the density of the myocardium in normal CTA or in test bolus data acquisitions [10]. All these authors found good correlation, with nuclear medicine or MRI serving as the gold standard.…”
mentioning
confidence: 99%